Safety of eribulin mesylate and concomitant radiotherapy for metastatic breast cancer: a single-center experience. (May 2016) - Meattini, Icro; Desideri, Isacco; Di Cataldo, Vanessa; Francolini, Giulio; De Luca Cardillo, Carla; Scotti, Vieri; Loi, Mauro; Detti, Beatrice; Mangoni, Monica; Agresti, Benedetta; Baldazzi, Valentina; Greto, Daniela; et al.
Aim: This study evaluates, for the first time, the safety of eribulin in metastatic breast cancer patients concomitantly treated with palliative radiotherapy (RT).Patients & materials: A total of 17 patients were pretreated for metastatic breast cancer. Patients received eribulin mesylate and bone RT.Results: The most frequent grade 3 hematologic adverse events were neutropenia (56%) and anemia (20%). Mean pain score decreased from 2 (baseline) to 0.7 (end of observation). Analgesic score remained stable (1.8 vs 1.6). Bone pain scores dropped within a few weeks and remained below baseline values throughout the analysis. The overall response rate was 29%, and the clinical benefit rate was 59%.Conclusion: Eribulin is characterized by a manageable safety profile also when combined with palliative RT.